Improving Biocompatibility of Polyurethanes Apply in Medicine Using Oxygen Plasma and Its Negative Effect on Increased Bacterial Adhesion - Kamil Drożdż; Monika Gołda-Cępa; Paulina Chytrosz-Wróbel; Andrzej Kotarba; Monika Brzychczy-Włoch (International Journal of Biomaterials)
Polyurethanes (PUs) are versatile polymers used in medical applications due to their high flexibility and fatigue resistance. PUs are widely used for synthetic blood vessels, wound dressings, cannulas, and urinary and cardiovascular catheters. Many scientific reports indicate that surface wettability is crucial for biocompatibility and bacterial adhesion. The use of oxygen plasma to modify PUs is advantageous because of its effectiveness in introducing oxygen-containing functional groups, thereby altering surface wettability. The purpose of this study was to investigate the effect of the modification of the oxygen plasma of polyurethane on its biocompatibility with lung tissue (A549 cell line) and the adhesion of Gram-positive bacteria (S. aureus and S. epidermidis). The results showed that the modification of polyurethane by oxygen plasma allowed the introduction of functional groups containing oxygen (-OH and -COOH), which significantly increased its hydrophilicity (change from 105° ± 2° to 9° ± 2°) of PUs. Surface analysis by atomic force microscopy (AFM) showed changes in PU topography (change in maximum height from ∼110.3 nm to ∼32.1 nm). Moreover, biocompatibility studies on A549 cells showed that on the PU-modified surface, the cells exhibited altered morphology (increases in cell surface area and length, and thus reduced circularity) without concomitant effects on cell viability. However, serial dilution and plate count and microscopic methods confirmed that plasma modification significantly increased the adhesion of S. aureus and S. epidermidis bacteria. This study indicate the important role of surface hydrophilicity in biocompatibility and bacterial adhesion, which is important in the design of new medical biomaterials.